Laleonectes vocans - Coelho, Petrônio Alves; Almeida, Alexandre Oliveira De; Bezerra, Luis Ernesto Arruda (Zenodo, 2008)
Laleonectes vocans (A. Milne-Edwards, 1878) Western Atlantic: Gulf of Mexico, West Indies and Brazil (Bahia to Rio de Janeiro). Central Atlantic: Ascension I. Eastern Atlantic: Madeira I., Cape Verde, São Tomé and Príncipe, and Annobon (Manning & Chace 1990; Melo 1996; Serejo et al . 2006). Occurrence in northern and northeastern Brazil: BA: Serejo et al . (2006). : Published as part of Coelho, Petrônio Alves, Almeida, Alexandre Oliveira De & Bezerra, Luis Ernesto Arruda, 2008, Checklist of the marine and estuarine Brachyura (Crustacea: Decapoda) of northern and northeastern Brazil, pp. 1-58 in Zootaxa 1956 (1) on page 29, DOI: 10.11646/zootaxa.1956.1.1, http://zenodo.org/record/5241063 : {"references": ["Milne-Edwards, A. (1878) Etudes sur les Crustaces Podophthalmaires de la region mexicaine. Recherches Zoologiques pour Servir a l'Histoire de la Faune de l'Amerique Centrale et du Mexique, 5, 121 - 184.", "Manning, R. B & Chace, Jr., F. A. (1990) Decapod and Stomatopod Crustacea from Ascension Island, South Atlantic Ocean. Smithsonian Contributions to Zoology, 503, 1 - 91.", "Melo, G. A. S. (1996) Manual de identificacao dos Brachyura (caranguejos e siris) do litoral brasileiro. Editora Pleiade, Sao Paulo, 603 pp.", "Serejo, C., Young, P. S., Cardoso, I., Tavares, C. R. & Abreu, C. R., Jr. (2006) Filo Arthropoda, Subfilo Crustacea. In: Lavrado, H. P. & Ignacio, B. L. (Eds), Biodiversidade bentonica da regiao central da Zona Economica Exclusiva Brasileira. Museu Nacional, Rio de Janeiro, pp. 299 - 337."]}